No genetic causal relationship between acne and prostate cancer through Mendelian randomization combined with meta-analysis - He, Mingyang; Wang, Xin; Wang, Dongbin; Wang, Yaxuan; Qi, Jinchun; Jia, Jianghua; Zhang, Ming; Meng, Qingsong; Yan, Bowen; Guo, Heyang; Qu, Changbao (Frontiers in Oncology, 2024)
BackgroundPrevious observational studies regarding the relationship between acne and prostate cancer have reported inconsistent results. As such studies are prone to biases, we conducted this Mendelian randomization (MR) analysis to better explore the causal association between acne and prostate cancer.MethodsThe genetic data for assessing acne were acquired from the largest genome-wide association study (GWAS) of acne by far, and the genetic data for assessing prostate cancer were acquired from the FinnGen consortium, UK Biobank, European Bioinformatics Institute, and IEU OpenGWAS project. We performed two-sample MR analyses using data from these GWASs followed by a meta-analysis to provide an overall evaluation. The primary MR methods used included inverse variance weighted, MR-Egger, and weighted median. Leave-one-out sensitivity tests, Cochran’s Q tests, and MR-Egger intercept tests were used to bolster the robustness of the MR results.ResultsThrough MR combined with meta-analysis, our study found no genetic causal relationship between acne and prostate cancer (p=0.378; odds ratio=0.985; 95% confidence interval, 0.954–1.018). Sensitivity tests ensured the robustness of this result.ConclusionAcne should not be considered as a morbidity hazard factor for prostate cancer.